1993
DOI: 10.1192/bjp.162.5.651
|View full text |Cite
|
Sign up to set email alerts
|

ImpairedIn VivoImmune Responses in Patients with Melancholia

Abstract: Previous attempts to establish a relationship between impaired cell-mediated immunity (CMI) and major mood disorders have been limited by a failure to explore the relevance of depressive subcategories or to assess CMI by in vivo methods. In this case-control study CMI was assessed in 57 patients with major depression (31 with melancholic, 26 with non-melancholic disorders), and in age- and sex-matched controls by both in vitro and in vivo immunological techniques. Compared with control subjects and patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 20 publications
5
26
0
Order By: Relevance
“…Most studies examining biological differences (including inflammatory markers) in melancholic patients have made comparisons with symptom-defined groups with nonmelancholic depression, atypical depression, or nondepressive controls 911,18,27,2932,34,35,68. Such studies have generally reported hypercortisolemia and other hypothalamic-pituitary-adrenal axis changes in melancholic patients11,18,32,34,69 but contradictory or less robust results in relation to inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies examining biological differences (including inflammatory markers) in melancholic patients have made comparisons with symptom-defined groups with nonmelancholic depression, atypical depression, or nondepressive controls 911,18,27,2932,34,35,68. Such studies have generally reported hypercortisolemia and other hypothalamic-pituitary-adrenal axis changes in melancholic patients11,18,32,34,69 but contradictory or less robust results in relation to inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…This test comprises a convenient plastic applicator with 7 ubiquitous antigens (tetanus, diphtheria, streptococcus, tuberculin, candida, trichophyton, and proteus) and a glycerine control preloaded in eight tined heads (7). A decline in immune function, associated with severe (melancholic) depression (8,9), wintering in the Antarctic (10), and perceived distress (11), has been demonstrated using this apparatus.…”
Section: Introductionmentioning
confidence: 97%
“…Such effects were particularly marked in depressed patients exhibiting melancholia (21,24), and at least some of the immune changes (altered lymphocyte proliferation) were independent of age, sleep disturbances, menopausal status, or prior treatment with benzodiazepines (7,24], Moreover, the reduced NK cell activity associated with major depression may be abrogated with symptom remission (25). It is unlikely that the immunosuppression seen among inpatients was due to institutionalization (21,26) because the reduced NK cytotoxicity was not evident in hospitalized schizophrenic patients (27,28).…”
Section: Introductionmentioning
confidence: 98%